2020
DOI: 10.3390/ijms21041295
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Cannabidiol Administration Fails to Diminish Blood Pressure in Rats with Primary and Secondary Hypertension Despite Its Effects on Cardiac and Plasma Endocannabinoid System, Oxidative Stress and Lipid Metabolism

Abstract: We investigated the influence of cannabidiol (CBD) on blood pressure (BP) and heart rate (HR) in spontaneously (SHR) and deoxycorticosterone (DOCA-salt) hypertensive rats. Hypertension was connected with increases in cardiac and plasma markers of lipid peroxidation in both models, whereas cardiac endocannabinoid levels decreased in SHR and increased in DOCA-salt. CBD (10 mg/kg once a day for 2 weeks) did not modify BP and HR in hypertension but counteracted pro-oxidant effects. Moreover, it decreased cardiac o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
47
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(64 citation statements)
references
References 82 publications
(124 reference statements)
6
47
0
2
Order By: Relevance
“…We are the first researchers who simultaneously determined 13 endocannabinoids and endocannabinoid-related lipids in the lungs (levels of OEA, SEA, HEA, DEA, 2-LG, DHEA, POEA and EPEA have never been determined in the lung). We confirmed that similarly to the lungs of rabbits [ 34 ], rats [ 35 ], mice [ 36 ] and rat hearts [ 16 ], the lungs’ 2-AG concentration was higher (by about 100 times) than the concentration of the well-known endocannabinoid AEA. Moreover, we noticed a similar ordering of endocannabinoid concentrations in rat lungs (the current study) and heart [ 16 ]: 2-AG > PEA ≈ OEA > AEA > LEA ≈ SEA ≈ POEA ≈ NAGly > DHEA ≈ DEA ≈ HEA ≈ 2-LG.…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…We are the first researchers who simultaneously determined 13 endocannabinoids and endocannabinoid-related lipids in the lungs (levels of OEA, SEA, HEA, DEA, 2-LG, DHEA, POEA and EPEA have never been determined in the lung). We confirmed that similarly to the lungs of rabbits [ 34 ], rats [ 35 ], mice [ 36 ] and rat hearts [ 16 ], the lungs’ 2-AG concentration was higher (by about 100 times) than the concentration of the well-known endocannabinoid AEA. Moreover, we noticed a similar ordering of endocannabinoid concentrations in rat lungs (the current study) and heart [ 16 ]: 2-AG > PEA ≈ OEA > AEA > LEA ≈ SEA ≈ POEA ≈ NAGly > DHEA ≈ DEA ≈ HEA ≈ 2-LG.…”
Section: Discussionsupporting
confidence: 75%
“…Chronic CBD 10 mg/kg/day administration was effective in the modification of cardiac and plasma endocannabinoid levels in two models of systemic hypertension [ 16 ] and exerted beneficial cardiovascular effects in diabetic and septic rats, in mice with diabetic- and doxorubicin-induced cardiomyopathy and experimental autoimmune myocarditis (see [ 16 ]). We decided to examine the protective but not therapeutic effect of CBD, because three weeks after MCT administration rats exhibited a higher mortality rate [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations